Mentoring and skill development in e-Internships. Issue 2 (8th April 2020) - Jeske, Debora; Linehan, Carol
Abstract : Purpose: Many employers experiment with virtual working modes for project-based work. Virtual internships are one such mode that is gaining increasing popularity worldwide, particularly e-internships that require remote working with employers. However, little is known about the extent to which e-internships present learning opportunities to such e-interns. Design/methodology/approach: The current study examined mentoring experiences among a cross-sectional sample of 158 e-interns working for different companies. Data were collected using an online survey in two data collection rounds. Findings: The length of the e-internships did not increase mentoring satisfaction, but the likelihood of e-interns having a mentor was higher the longer the e-internships. Mentoring was offered irrespective of working hours per week. Mentoring increased reported skill development, particularly in relation to their communication skills and their ability to think strategically about problems. In addition, mentored e-interns were more likely to have opportunities to cooperate with and help others. They likewise had opportunities to share information, knowledge and experiences. Research limitations/implications: The study recruited interns from various countries. Potentially relevant cultural differences were not explored as part of this study. Practical implications: The results demonstrate that the benefits of mentoring observed in relation to traditional internships can be fostered in e-internships. E-internships represent an opportunity for managers and employees, regardless of company size, to become mentors. E-internships thus represent another work-integrated as well as work-applied learning and skill development opportunity that creates additional options for many interns and organisations alike. Originality/value: The evidence suggests that mentoring is becoming a regularly available feature for virtual and temporary workers such as e-interns, many of which are hired for short-term projects. As remote working has become a standard practice, e-internships are on the rise – and worthy of further study in order to promote best practices.